Peran Keluarga Dalam Menjunjung Tinggi Sikap Bela Negara Terhadap Paham Radikalisme Dalam Media Sosial - Eriz Syawaldi; Gema Permana Rahman; Muhamad Afifullah; Irwan Triadi (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Radicalism is an internal threat to a country, because it triggers acts of terrorism, so it is necessary to instil a sense of nationalism in every family, because radicalism has the impact of national disintegration. This research uses a normative juridical approach method with descriptive analytical analysis of legal materials. The results of this study found that radicalism can be spread through social media massively, because Radicalism can appear unlimited in space and time. Therefore, efforts that can be made to reduce radicalism in the family, by introducing science properly and correctly, understanding science properly and correctly, minimising social inequality, maintaining unity and integrity, supporting peace actions, playing an active role in reporting radicalism and terrorism, increasing understanding of living together, filtering the information obtained.